Characterization and application of a novel xylanase from Halolactibacillus miurensis in wholewheat bread making - Zhang, Yaping; Liu, Chun; Yang, Manli; Ou, Zuyun; Lin, Ying; Zhao, Fengguang; Han, Shuangyan (Frontiers in Bioengineering and Biotechnology, 2022)
The presence of arabinoxylan in wholewheat flour affects its quality significantly. Here, an efficient arabinoxylan hydrolytic enzyme, Hmxyn, from Halolactibacillus miurensis was identified and heterologously expressed in pichia pastoris. Moreover, its relevant properties, including potential application in the wholewheat bread were evaluated. Recombinant Hmxyn exhibited maximal activity at 45 °C and pH 6.5, and was stable at mid-range temperature (< 55°C) and pH (5.5-8.0) conditions. Hmxyn had a clear hydrolysis effect on wheat arabinoxylan in dough and caused the degradation of the water-unextractable arabinoxylan, which increased the content of wheat soluble arabinoxylan of dough. The fermentation characteristics results and microstructure analysis revealed that Hmxyn improved the organizational structure and air holding capacity of fermented dough, thus promoting the dough expansion. Baking experiments further showed that Hmxyn significantly increased specific volume- and texture-linked properties of wholewheat breads. This study indicates the application potential of Hmxyn in the preparation of wholewheat bread.